Hemodiálise: análise da qualidade de vida de indivíduos renais crônicos - Silva, Pollyanna (2020)
Chronic kidney disease is considered a socioeconomic problem, causing limitations and impairment, in addition to presenting high morbidity and mortality and generating major impacts on patients' daily lives and quality of life. The aim of the present study is to assess the quality of life in patients with chronic kidney disease undergoing hemodialysis. This was a cross-sectional analytical study with a quantitative approach. The research was conducted at the Hemodialysis Clinic in the city of Porangatu/GO, with 102 patients undergoing hemodialysis, using the instruments Kidney Disease and Quality of Life Short Form (KDQOL-SF) and a socio-economic and demographic questionnaire. It was possible to collect from each interviewed participant, considering sex, age, personal income, education, comorbidities, use of regular medications, family history, life habits, physical activity, commuting to the hemodialysis clinic, hemodialysis plan and eating vegetables, fruits and vegetables, lifestyle changes due to hemodialysis. The average, lower and upper values of the generic and specific dimensions of the KDQOL-SF are presented. In the generic dimensions, the highest summary score was for emotional well-being, with an average of 68.51, 72.12 for men and 61.6 for women. Other significant scores were: social function (63.73), energy and fatigue (61.18), pain (55.59), general health (52.60). The lowest average scores obtained were physical functioning (40.05), emotional functioning (20.59) and physical functioning (12.99). In the specific dimensions of the KDQOL-SF, the highest mean scores were: stimulus by the dialysis team (95.96), patient satisfaction (90.36), cognitive function (78.56) and list of symptoms and problems (75.12). The lowest average scores obtained were in the professional role (7.35), in the burden of kidney disease (37.56) and effects of kidney disease (48.74). The research assessed the quality of life of people with chronic kidney disease and identified the determining factors for the improvement or worsening of the clinical picture, enabling subsidies in the implementation of new efficient strategies in teaching, in practice and in studies related to the person with chronic kidney disease undergoing hemodialysis treatment, aiming to improve their living conditions